Identification of Motivation and Self-Actualization Dance Studio Students - I Gusti Ngurah Sudibya; Gatut Rubiono; Ida Ayu Wayan Arya Satyani; Nurida Finahari; Ida Made Dwipayana (Fakultas Bahasa dan Seni UNP, 2023)
Student’s motivation in participating in dance lessons in a dance studio can determine the success of the learning process. This study aims to identify the motivation and self-actualization of dance studio students. Research respondents are 220 dance studio students from Denpasar and Buleleng Bali. The research was conducted using a questionnaire distributed through the google form application. The questionnaire consists of 8 question items with predetermined answer choices. The results of the study indicate that hobbies are the main reason for students to choose dance. The self-actualization of students is shown to be sufficient for them to be involved in dance performances.